The “Jewish Sibyl” in Clement of Alexandria’s Protrepticus - Golovatskaya, Sophia (Hyperboreus, 2023)
The article examines passage 71. 4 of the Protrepticus by Clement of Alexandria, in which the pagan Sibyl is called a “Jewish prophetess”. The passage appears unique, because no other known Christian text before Clement addresses the Sibyl as a Jewish prophetess. Moreover, the “Jewish Sibyl” of the Protrepticus contradicts the opinion prevailing among Christian apologists that the Sibyl was a divinely inspired, but still pagan prophetess, the view Clement himself shares in some passages of the Stromateis. There was an attempt to explain away this extraordinary idea by supposing that Clement has in view the pagan Sibyl who makes prophecies about Jews (R. Buitenwerf). Other scholars rightly rejected this attempt. It was also proposed, albeit without detailed argumentation, that Clement was inﬂuenced by Book 3 of the Sibylline Oracles, where the Sibyl speaks of herself as a relative of Noah who settled in Babylon after the ﬂood, but later migrated from Babylon to Greece and became known there as the Sibyl from Erythrae in Asia Minor (N. Zeegers-Vander Vorst). By examining various works by Clement as well as texts by ancient and Christian authors, the author of the present paper attempts to endorse this latter proposal. Relying on the statements of Lactantius about the Sibyl from Babylon, which are connected with his quotations of fragments from the Sibylline Oracles, attributed by him to the third book, one can infer that fragment 1 of the Oracles belonged to the third book in the time of Clement. Therefore, it can be stated with suﬃcient certainty that Clement’s designation of the Sibyl as a Jewish prophetess in Protr. 71. 4, where he quotes just vv. 10–13 of this fragment, goes back to the Sibyl’s characterization of herself as a relative of Noah in Book 3 of the Oracles. This also makes it probable that Clement was familiar with this book of the Oracles directly, without any mediators.